Micro-computed-tomography-guided analysis of in vitro structural modifications in two types of 45S5 bioactive glass based scaffolds - Westhauser, Fabian; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash (Materials, 2017)
Three-dimensional 45S5 bioactive glass (BG)-based scaffolds are being investigated for bone regeneration. Besides structural properties, controlled time-dependent alteration of scaffold morphology is crucial to achieve optimal scaffold characteristics for successful bone repair. There is no in vitro evidence concerning the dependence between structural characteristics and dissolution behavior of 45S5 BG-based scaffolds of different morphology. In this study, the dissolution behavior of scaffolds fabricated by the foam replica method using polyurethane foam (Group A) and maritime sponge Spongia Agaricina (Group B) as sacrificial templates was analyzed by micro-computed-tomography (µCT). The scaffolds were immersed in Dulbecco’s Modified Eagle Medium for 56 days under static cell culture conditions and underwent µCT-analysis initially, and after 7, 14, and 56 days. Group A showed high porosity (91%) and trabecular structure formed by macro-pores (average diameter 692 µm ± 72 µm). Group-B-scaffolds were less porous (51%), revealing an optimal pore size distribution within the window of 110-500 µm pore size diameter, combined with superior mechanical stability. Both groups showed similar structural alteration upon immersion. Surface area and scaffold volume increased whilst density decreased, reflecting initial dissolution followed by hydroxycarbonate-apatite-layer-formation on the scaffold surfaces. In vitro- and/or in vivo-testing of cell-seeded BG-scaffolds used in this study should be performed to evaluate the BG-scaffolds’ time-dependent osteogenic properties in relation to the measured in vitro structural changes.